Recoding Life : Information and the Biopolitical. - Tamminen, Sakari. (Taylor & Francis Group, 2018)
This book addresses the unprecedented convergence between the digital and the corporeal in the life sciences and turns to Foucault' biopolitics in order to understand how life is being turned into a technological object. The authors argue that through discussions of political theories of sovereignty and related geopolitical conceptions of nature and society, we can understand how crucially important it is that life is constantly unsettling and disrupting the established and familiar ordering of the material world and the related ways of thinking and acting politically. As such, the book will appeal to scholars of science and technology studies, as well as scholars of the sociology, philosophy and anthropology of science, who are seeking to understand social and technical heterogeneity as a characteristic of the life sciences.